Prospektus Perusahaan dan Keputusan Investasi: Studi Empiris Perusahaan yang Terdaftar di Bursa Efek Jakarta - Hadri Kusuma (Jurnal Siasat Bisnis, 2001)
This paper reports the result of the empirical investigation on the usefulness of company prospectuses for investment decisions. The invesment decisions are measured in terms of initial returns for the investment decision in the primary stock market, and 15-day mean adjusted returns after Initial public offering for the investment decision in the secondary stock market. The data of the prospectus used are accounting and non-accounting information. Based on the sample of 91 firm-year observations, the result shows that non-accounting information of the prospectus is relevant for the investment decision in the primary stock market. As well, both accounting and non-accounting information is useful for the investment decision in the secondary stock market. Eventhough some ceveats appear in the study and preclude the generalization, the results are robust.Key Words: Underpricing, initial return, mean adjusted return, underwriter, auditor, listing period, standard diviation, company age, percentage of offered stock value, profitibility, financial leverage, solvability, and investment decisions.